The Politics of Non-Translation: A Case Study in Anglo-Portuguese Relations - Ferreira Duarte, João (TTR)

(untitled) (Association canadienne de traductologie, 2000)
AbstractThe Politics of Non-Translation: A Case Study in Anglo-Portuguese Relations — One of the most fruitful paths opened up by the functionalist, target-oriented, turn in the study of the translation has been the possibility of taking into theoretical and analytical account objects that are epistemologically identifiable as being empirically absent. Non-translation, both at a lexical or a textual level, becomes thus available for research. In this context, the present paper has a double purpose: to describe a set of non-translation categories and to discuss a case of ideologically driven absence of translation. This case study concerns an intriguing episode in Shakespeare reception in Portugal: the almost complete lack of new translations from Shakespeare's works into the last decade of the nineteenth century following a fifteen-year period of intense translational activity and unprecedented popularity enjoyed by Shakespeare in the target culture. It was found that such a striking instance of non-translation was due to a nation-wide wave of anti-British nationalism that swept the country in the wake of colonial rivalry over a portion of territory in Southern Africa.